Burden of drug induced allergic reactions: a 3-year experience in a tertiary care hospital - Mukherjee, Shatavisa; Tripathi, Santanu Kumar (International Journal of Research in Medical Sciences, 2020)
Background: DIARs includes a wide spectrum of immunologically-mediated hypersensitivity reactions with varied mechanisms and clinical manifestations. Besides affecting a patient’s quality of life, it may also lead to increased treatment cost and length of hospitalization. The present study aims to provide an overview of drug induced allergic reactions experienced in a tertiary care set-up. Methods: A prospective observational outcome research was conducted over a 3-year period on patients encountering drug induced allergic reactions, who has been analysed for their spectrum of presentation, clinical outcomes (including severity, management and outcome of reaction), economic outcomes (including cost of treatment) and humanistic outcomes (including assessment of quality of life). Results: Drug induced allergic reactions accounts for 2.71% of total hospitalization in this study period. While majority reactions were moderate in severity grading, most were preventable. Direct cost of treating such preventable reactions were much higher along with increased indirect cost (due to prolonged hospitalization) adding to economic burden. Quality of life in patients encountering such reactions was also compromised as assessed using EQ-VAS. Conclusions: Prompt identification, consultation, cessation of culprit drug, management and patient counselling can act as strategies to minimize the burden of these reactions on society and healthcare system at large.